Elchemy - Saroj, Manasi (ATLAS SkillTech University, 2024)
This report serves as a testament to the exceptional learning opportunities that Elchemy has offered. Through my involvement in various roles, I gained a comprehensive understanding of market strategy and research analysis, embracing the challenges and contributing to the company's growth and success. The experience exposed me to a multitude of tasks, including data analysis, market research, and strategic planning, honing my analytical skills and strategic thinking.
Project Report on Elchemy (2022-24)
Keywords: Elchemy; Analytics; Strategic Thinking